The effects of a symptom management program on symptom experience and physical function in Thai adults with chronic obstructive pulmonary disease: A single-blind randomized controlled trial study - Kochamat, Apinya; Harnirattisai, Teeranut; Juratovac, Evanne (Belitung Raya Foundation, Indonesia, 2024)
Background: Adults with Chronic Obstructive Pulmonary Disease (COPD) experience a range of unpleasant symptoms, including fatigue, dyspnea, sleep disturbances, anxiety, and depression, that are interrelated and impact one another. Developing a program to handle simultaneous symptoms poses challenges but offers advantages for adults with COPD in efficiently managing symptoms. Objective: This study aimed to determine the effects of a symptom management program on symptom experience and physical function in Thai adults with COPD. Methods: A randomized controlled trial (RCT) with a Repeated Measures design was performed. One hundred and two participants were allocated randomly to either the control group (n = 51) or the experimental group (n = 51). The experimental group received eight weeks of the symptom management program and usual care, while the control care group received only usual care. Data were collected from January 2023 to August 2023 at baseline, 4th weeks, and 8th weeks using the demographic data, the modified Medical Research Council (mMRC), the Pittsburgh Sleep Quality Index (PSQI), the Multidimensional Assessment of Fatigue (MAF), the Hospital Anxiety and Depression Assessment Scale (HADS), the COPD Assessment Test (CAT), and 6-Minute Walk Distance (6-MWD). The hypotheses were analyzed using Repeated Measures Multivariate Analysis of Variance (MANOVA). Results: The symptom management program significantly impacted the experimental group’s symptom experience and physical function at Weeks 4 and 8 (F = 5.257, p <0.001). There were significantly improved mean scores for the mMRC, MAF, 6MWD, and CAT (p <0.001, p <0.05). No statistically significant differences were observed in the PSQI, HADS-Anxiety, and HADS-Depression over time. Conclusion: Implementing a symptom management program can help patients with COPD efficiently manage their symptoms. In clinical settings, nurses should integrate this program into routine nursing care to enhance the quality of life for patients suffering from COPD. The program can help patients preserve physical functionality while reducing dependence on family and society. Trial Registry Number: Thai Clinical Trials Registry (TCTR20230111006)